2014
DOI: 10.1590/1678-41626128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EGFR and HER-2 expressions in ductal carcinomas in situ in canine mammary glands

Abstract: Biomolecular evidence has shown that ductal carcinoma in situ (DCIS) may develop into invasive carcinoma of the canine mammary gland, and mutations in proto-oncogenes HER2 and EGFR; two members of the family of epidermal growth factor receptors, may be involved in this process. The purpose of this study was the characterization of the immunohistochemical expression of the EGFR and HER2 proteins in the process of neoplastic transformation, supposedly present in ductal carcinomas in situ in canine mammary glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
8
1
2
Order By: Relevance
“…Furthermore, the frequency of EGFR expression did not differ between primary mammary carcinomas with lymph node metastasis and without metastasis. EGFR expression has been suggested to be an early event in the carcinogenesis of canine mammary carcinoma, which could explain the findings of the present study (Bertagnolli et al, 2011;Ferreira et al, 2012;Silva et al, 2014). However, an association between the positivity to EGFR and the presence of lymph node metastasis was observed by Guimarães et al (2014) but not by Gama et al (2009).…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, the frequency of EGFR expression did not differ between primary mammary carcinomas with lymph node metastasis and without metastasis. EGFR expression has been suggested to be an early event in the carcinogenesis of canine mammary carcinoma, which could explain the findings of the present study (Bertagnolli et al, 2011;Ferreira et al, 2012;Silva et al, 2014). However, an association between the positivity to EGFR and the presence of lymph node metastasis was observed by Guimarães et al (2014) but not by Gama et al (2009).…”
Section: Discussioncontrasting
confidence: 60%
“…HER2 protein overexpression has been determined to be both predictive for tumor response to HER2-targeted treatments and prognostic for disease outcome in human patients ( 93 ). Several studies have suggested that ~35% of malignant CMT have either HER2 gene or protein expression ( 94 – 97 ) and that HER2 expression is associated with histological grade, proliferation index and tumor size ( 94 , 96 , 98 ). Human and canine genome sequencing has identified significant homology between the HER2 antigens in both species and although further research is needed, results such as these suggest that human-based immunotherapies (e.g., pertuzumab or trastuzumab) or human developed tyrosine kinase inhibitors, could be successfully employed in HER2 + CMT ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that CMT could be translational models of HBC where HER2 overexpression occurs in the absence of gene amplification (135). HER2 expression has been correlated with mitotic index, histological grade and tumor size (131,133,136). Although HER2 expression is thought to be associated with poor prognosis (137) some studies have shown no difference in HER2 expression between benign and malignant tumors (132,138,139).…”
Section: Signaling Receptors and Associated Pathwaysmentioning
confidence: 99%